2013
DOI: 10.1097/nmd.0b013e3182a5bf1d
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Efficacy, Expressed Emotion, and the Course of Schizophrenia

Abstract: Although it is clear that expressed emotion (EE) is associated with the course of schizophrenia, proposed models for this association have struggled to account for the relationship between the EE index of emotional overinvolvement (EOI) and relapse. To expand our understanding of the EOI-relapse association, we first attempted to replicate the finding that the EOI-relapse association is curvilinear among 55 Mexican-Americans with schizophrenia and their caregiving relatives. Second, we evaluated whether the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…For these reasons, we only included data from studies that used the CFI. It is important to note that one study that used the CFI (Breitborde, López, Aguilera, & Kopelowicz, ) was excluded from the analysis because only the emotionally overinvolved component of EE was measured. Therefore, participants were not grouped into high versus low EE (like the other studies used in this paper), but rather as high versus low EOI.…”
Section: Methodsmentioning
confidence: 99%
“…For these reasons, we only included data from studies that used the CFI. It is important to note that one study that used the CFI (Breitborde, López, Aguilera, & Kopelowicz, ) was excluded from the analysis because only the emotionally overinvolved component of EE was measured. Therefore, participants were not grouped into high versus low EE (like the other studies used in this paper), but rather as high versus low EOI.…”
Section: Methodsmentioning
confidence: 99%
“…Although most studies examine either EE or caregiver burden, there are only a handful of studies that integrate the two family roles in a single study. For example, Breitborde, López, Aguilera, and Kopelowicz () brought the caregiver burden focus to a study of expressed emotion. Specifically, in a longitudinal design, they found that for Mexican American families, emotional overinvolvement was related to more family burden and, in turn, worse health outcomes for caregivers over a one‐year period.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of EOI may be due to its impairment on patients’ agency. Caregivers high in EOI tend to perceive the patient as less capable of participating and completing tasks associated with the recovery process ( 64 ). This may lead the patients to lose confidence in getting back to society and reduce participation in activities that help improve their QoL.…”
Section: Discussionmentioning
confidence: 99%